Neural Indices of Vowel Discrimination in Monolingual and Bilingual Infants and Children. Issue 6 (November 2019) - Yu, Yan H.; Tessel, Carol; Han, Henry; Campanelli, Luca; Vidal, Nancy; Gerometta, Jennifer; Garrido-Nag, Karen; Datta, Hia; Shafer, Valerie L.
Abstract : Objectives: To examine maturation of neural discriminative responses to an English vowel contrast from infancy to 4 years of age and to determine how biological factors (age and sex) and an experiential factor (amount of Spanish versus English input) modulate neural discrimination of speech. Design: Event-related potential (ERP) mismatch responses (MMRs) were used as indices of discrimination of the American English vowels [ε] versus [I] in infants and children between 3 months and 47 months of age. A total of 168 longitudinal and cross-sectional data sets were collected from 98 children (Bilingual Spanish–English: 47 male and 31 female sessions; Monolingual English: 48 male and 42 female sessions). Language exposure and other language measures were collected. ERP responses were examined in an early time window (160 to 360 msec, early MMR [eMMR]) and late time window (400 to 600 msec, late MMR). Results: The eMMR became more negative with increasing age. Language experience and sex also influenced the amplitude of the eMMR. Specifically, bilingual children, especially bilingual females, showed more negative eMMR compared with monolingual children and with males. However, the subset of bilingual children with more exposure to English than Spanish compared with those with more exposure to Spanish than English (as reported by caretakers) showed similar amplitude of the eMMR to their monolingual peers. Age was the only factor that influenced the amplitude of the late MMR. More negative late MMR was observed in older children with no difference found between bilingual and monolingual groups. Conclusions: Consistent with previous studies, our findings revealed that biological factors (age and sex) and language experience modulated the amplitude of the eMMR in young children. The early negative MMR is likely to be the mismatch negativity found in older children and adults. In contrast, the late MMR amplitude was influenced only by age and may be equivalent to the Nc in infants and to the late negativity observed in some auditory passive oddball designs.